THE EFFECT OF ELECTRONIC WORD OF MOUTH ON CONSUMER BUYING DECISION IN LAZADA - Maria, Keles Dikna; Kindangen, Paulus; Rumokoy, Farlane S. (Universitas Sam Ratulangi, 2016)
These past few decades, the internet has developed into a vast global market place for the trading of goods and services. People are doing business online and it has become more easy and fast due to internet development. Online shopping has grown in popularity, mainly because people find it convenient and easy toÂ shop anytime and anywhere. These new technologies also altered our way to communicate and to interconnect with people.Â Internet advancement has developed and transformed Word-of-Mouth into something much more influential and fast-spreading, Electronic Word of Mouth (E-WOM). This research is conducted in order to analyze the influence of E-WOM using experience, perceived credibility, and customer susceptibility to interpersonal influence on consumer buying decision. The sample of this research is people who have been shopped in Lazada online shop as many as 60 respondents of purposive sampling. The result of this research reveals that experience is the only variable that has a significant influence on consumer buying decision. This research suggests that the e-business firms should further expose the reviews section to users. Â Keywords: electronic, word-of-mouth, experience, credibility, susceptibility, buying decision